2020
DOI: 10.1055/a-1072-4853
|View full text |Cite
|
Sign up to set email alerts
|

Optical diagnosis of diminutive polyps in the Dutch Bowel Cancer Screening Program: Are we ready to start?

Abstract: w.vandewetering@maastrichtuniversity.nl ABSTR AC T Background and study aims Implementation of optical diagnosis of diminutive polyps may potentially increase the efficacy and cost-effectiveness of colonoscopies. To adopt such strategy in clinical practice, the Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) thresholds provide the basis to be met: ≥ 90 % negative predictive value (NPV) for diagnosis of adenomatous histology and ≥ 90 % agreement on surveillance intervals. We evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Winkens 5 , P. Aepli 6 , B. Hayee 7 , A.B. Pischel 8 , M. Stefanovic 9 , S. Subramaniam 10 , P. Bhandari 10…”
Section: Improving Optical Diagnosis Of Colorectal Polyps Using Compumentioning
confidence: 99%
See 2 more Smart Citations
“…Winkens 5 , P. Aepli 6 , B. Hayee 7 , A.B. Pischel 8 , M. Stefanovic 9 , S. Subramaniam 10 , P. Bhandari 10…”
Section: Improving Optical Diagnosis Of Colorectal Polyps Using Compumentioning
confidence: 99%
“…This study has several strengths. First, both experts and novices performed the optical diagnosis of CRPs, while previous studies mainly focused on highly selected groups of experts [3][4][5]. Adding novices increased the generalizability of this study.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Developed in 1999, NBI has been reported to provide valuable information regarding the histology of polyps detected during colonoscopy [ 4 ]. Since then, many studies have reported the efficacy of NBI-assisted optical diagnosis of colorectal polyp histology [ 5 7 ]. Moreover, NBI-assisted optical diagnosis may enable immediate determination of the appropriate surveillance interval with reduction in the risk of adverse events and health care expenditure [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%